A reception analysis in Barangay Lubogan Toril District Davao City understanding the viewers' consumption of the television tabloid talk show face to face - Barabat, Cheenne Mae G.
The issues of how audiences consume media and factors that affect their choice of media content have presented many questions of communication scholars. Though there are numerous studies that have been made, there have been no studies on how audiences consume tabloid talk shows in the Philippines, specifically Face to face. Therefore, this study was conducted to evaluate: (a) why the Filipino audiences consume face to face, (b) what specific parts of the program that they like most/least, and (c) what uses and gratifications are met by watching the show. The researcher conducted a survey and focus interview to gather the data in this study the result of the study shows that the show gives gratification to audience. The first factor why the audience watch the show is the information they get which includes the advices, lessons, and any knowledge acquired from the show because the viewers believed that it does not only help the guests, but also them, as viewers. The respondents also considered humor and personal references as part of the reasons they watch the program. The result also showed that one of the parts of the program that some respondents like is the physical blows, though there were also respondents who like it least since it is bad for the children. The study showed that face to face therefore provided the audience with their needs of information, relatedness, and entertainment and the gratifications for media use are for surveillance, diversion, and personal identity. This recommends that the producers of tabloid talk shows should meet the needs of the viewers provided in this study. It also recommends further studies on this matter to other places in Davao City